Didactic equipment textbooks for technology subject to lower secondary level - LUKÁČOVÁ, Danka (Journal of Education, Technology and Computer Science, 2013)
It is now often discussed the quality of new textbooks for primary and secondaryschools. For the subject of technology (technical education) at lowersecondary level education teachers have used since 1999 one textbook and to the2012 the second textbook was released. We have examined how the didacticequipment’s of these books is and so we compared the new with the old one. Forthis purpose we used the method according to J. Prucha. Since the coefficient ofdidactic equipment from 2012 textbooks is 8% higher, it can be stated that thedidactic usefulness of a new textbook is greater.